The role of cherries in exercise and health. Issue 3 (27th May 2013) - Bell, P. G.; McHugh, M. P.; Stevenson, E.; Howatson, G.
<x xml:space="preserve">Abstract</x> Recently, cherries and cherry products have received growing attention within the literature with regard to their application in both exercise and clinical paradigms. Reported to be high in anti‐inflammatory and anti‐oxidative capacity, cherries and their constituents are proposed to provide a similar but natural alternative akin to over‐the‐counter non‐steroidal anti‐inflammatory drugs (NSAIDs) or analgesics. Within exercise paradigms, concern has been raised with regard to the use of products, which inhibit such inflammatory or oxidative actions, because of the possibility of the blunting of physiological training adaptations. Despite this, numerous scenarios exist both within exercise and clinical populations where a goal of optimal recovery time is more important than physiological adaptation. This review critically evaluates and discusses the use of cherries as a supplementation strategy to enhance recovery of muscle function, inhibit exercise‐induced inflammation, oxidative stress, and pain primarily; furthermore, the potential application of cherries to clinical populations is discussed.